Предмет: Алгебра,
автор: turrinshurra
Срочно помогите !!!!!!!!!!!!!!!!!!!!
Приложения:

Ответы
Автор ответа:
1
Відповідь:
cos²(2α) + ((1 + cos(2α)) * tg(α))² = cos²(2α) + ((1 + 2cos²(α)-1) * sin(α)/cos(α))² = cos²(2α) + ( 2cos²(α) * sin(α)/cos(α))² = cos²(2α) + (2cos(α)*sin(α))² = cos²(2α) + sin²(2α)
(cos³(α)-(4*cos³(α) - 3cos(α))/ cos(α) - (sin³(α) + sin(3α))/ - sin(α) = (-3cos³(α) + 3cos(α))/ cos(α) + (sin³(α) + sin(3α))/ sin(α) = -3cos³(α) + (-cos²(α) + 1)/ cos(α) + (sin³(α) + sin(3α))/ sin(α) = 3sin²(α) +(sin³(α) + sin(3α)/ sin(α) = 4sin³(α) + sin(3α))/ sin(α)
Похожие вопросы
Предмет: Беларуская мова,
автор: Mtanuxa
Предмет: Другие предметы,
автор: valeryashtygas
Предмет: Українська мова,
автор: ruzniavka
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: Dias051111